Avaliação da concentração do crédito BNDES para as empresas do setor sucroalcooleiro brasileiro entre 2002 e 2018 - Barboza, Caio César [UNESP]; Figueira, Sérgio Rangel Fernandes [UNESP] (Instituto de Economia da Universidade Estadual de Campinas, 2021)
The goal of the paper was to investigate how BNDES credit was distributed to the 100 largest companies, considering the 2012/2013 harvest, in sugarcane crushing, in the Brazilian sugar and alcohol sector in the period from 2002 to 2018. In addition, a comparative measurement was carried out considering the granting of BNDES credit and the amount of crushed sugarcane, the concentration ratio and the Gini coefficient. Lorenz curves were also constructed comparatively. In all the indicators measured, there was greater concentration and inequality in the granting of credit to the largest companies in relation to the smaller ones. Asymmetry was also observed in relation to access to credit, with the larger companies having greater access in relation to the smaller ones. All ten largest companies have borrowed from the BNDES. Of the fifty largest, thirty-two received credit from the BNDES. From the fifty-first to the hundredth group, seven companies received credit.

O objetivo do artigo foi o de averiguar como foi distribuído o crédito do BNDES para as 100 maiores empresas, considerando a safra 2012/2013, em moagem de cana-de-açúcar do setor sucroalcooleiro brasileiro no período de 2002 até 2018, mensurando-se ainda comparativamente a concessão de crédito do BNDES e a quantidade de moagem de cana-de-açúcar, a razão de concentração e o coeficiente de Gini. Construiu-se também, comparativamente, curvas de Lorenz. Em todos os indicadores mensurados constatou-se maior concentração e desigualdade na concessão de crédito para as maiores empresas em relação às menores. Observou-se ainda assimetria com relação ao acesso ao crédito, com os maiores tendo maior acesso em relação aos menores. As dez maiores empresas captaram crédito do BNDES. Dos cinquenta maiores, trinta e duas captaram crédito do BNDES. Do quinquagésimo primeiro ao centésimo grupo, sete grupos captaram crédito.
An analysis of the concentration of BNDES credit to Brazilian sugar and ethanol companies between 2002 and 2018
Keywords: Concentration; BNDES credit; Top 100 companies; Sugar and alcohol industry; Concentração; Crédito do BNDES; 100 maiores empresas; Setor sucroalcooleiro